Piloting an email-based resource package for job seekers with multiple sclerosis. Issue 9 (24th April 2017) - Dorstyn, Diana; Roberts, Rachel; Murphy, Gregory; Kneebone, Ian; Migliorini, Christine; Craig, Ashley; Hutchinson, Claire; Field, Deborah
Abstract: Purpose : Media-based rehabilitation provides a powerful opportunity to examine vocational behaviors in the disability sector. However, this research is preliminary at best. This paper reports pilot data.Method : Eighteen adults with multiple sclerosis (MS) accessed an email-delivered, resource-based package, Work and MS. Pre- and post-access vocational self-efficacy and identity (Job-Procurement Self Efficacy Scale, My Vocational Situation Scale- primary outcomes), life orientation and depressed mood ( Life Orientation Test – revised and Patient Health Questionnaire-9 – secondary outcomes) were assessed. Pre- and post-change scores were examined with Wilcoxon signed ranks tests and Hedges g effect sizes with associated 95% confidence intervals. Reliable change analyses were additionally calculated to determine the clinical significance of individual change scores.Results : Significant and positive effects were reported for vocational self-efficacy, identity, and optimism. Reliable change scores in one or more of these key outcomes were reported by 30% of the sample. Satisfaction with the content and delivery of the email-based intervention was also noted.Conclusions : Preliminary evidence suggests that Work and MS can help to promote vocational goals, interests and strengths among job seekers with a disability by providing a set of tools, information and linkages relating to vocational pursuits and career development. Replication with a randomized control design is indicated. Implications for Rehabilitation: Research indicates a high unemployment rate among working-age adults with MS. A combination of disease-specific, psychological, programmatic and societal variables contribute to employment instability in this group. This pilot study demonstrates that an e-mail-based resource package, Work and MS, provides an innovative and feasible option for promoting consumer engagement with vocational services and, potentially, improving vocational outcomes. Work and MS has potential applicability to other disability groups.